El Excentrico, 1975-06-20 - None::::::::::::::: (San Jose, California; Garcia Printing, 2023)
June 20, 1975. [20 de junio de 1975]. No volume or issue number. Cover has advertisement featuring a portrait of Hank Coca, owner of Furniture Discount House.